Observation and manipulation of CIGSe phase formation in a two stage sequential process - Schoenherr, Sven; Schoeppe, Philipp; Kusch, Alexander; Oertel, Michael; Reisloehner, Udo; Ronning, Carsten (Applied Physics Letters, 2019)
The formation process of the absorber layer in Cu(In,Ga)Se2-based (CIGSe) thin film solar cells is complex and still not understood in detail. Specifically, the Ga gradient of CIGSe solar cells has a strong impact on the efficiency. In a common sequential process, the gradient cannot be adjusted directly by a variation of the sputtered metal precursor layers. Therefore, CIGSe solar cells were produced in a two stage sequential process. The selenization was further split into two stages at different selenization temperatures in order to manipulate the phase formation. We observed that a variation of the selenization temperature in the first stage leads to absorber layers with significant changes in the Ga distribution and show that the formation of the CIGSe phase starts in the center of the deposited precursor layers and not at any interface to the back contact or at the surface.
CRIS-Team Scopus Importer:2023-04-20